Heat Properties of Polylactic Acid Biocomposites after Addition of Plasticizers and Oil Palm Frond Microfiber - Firda Aulya Syamani; Lisman Suryanegara; Wida Banar Kusumaningrum (Jurnal Kimia Sains dan Aplikasi, 2020)
Polylactic acid (PLA) is a biopolymer that can replace thermoplastic polymers such as polypropylene (PP) in various applications due to strength, young modulus, biocompatibility, biodegradability, good clarity, oil resistance, and oxygen barrier ability. However, PLA has some drawbacks, including brittle, high glass transition temperature (Tg), and low degradation and crystallization rates. Therefore, modification is needed with the addition of nucleating agents and plasticizers to overcome these limitations of PLA. This research aims to study the effect of plasticizers and microfibril cellulose of oil palm frond (OPF) on thermal stability and to review the crystallization kinetics of PLA biocomposites. Polyethylene glycol and triacetin were used as plasticizers. Thermal analysis was performed using Thermal Gravimetry analysis (TGA) and Differential Scanning Calorimetry (DSC). The crystallization kinetics study was analyzed using a modified Avrami model under non-isothermal conditions. PLAP4000 has better thermal stability than PLAP200 and PLAG with Tonset and Tmax values reaching 349.17°C and 374.68°C, respectively, which are close to pure PLA. All types of plasticizers influenced decreasing the Tg value in the range of 27–42%, whereas OPF microfiber addition contributes to a Tg reduction of 37-55 %. Crystallization kinetic study was informed for heterogeneous and simultaneous nucleation mechanisms with an n value range of about 2-3 for PLAP4000 and PLAOP4000. The crystallization rate was multiplied 4-9-fold for PLAOP200 and 2-3-fold for PLAOP4000.